Impact of Financial Ratios, Operational Efficiency, and Non-Performing Loans on the Profitability of Nepalese Commercial Banks - Sah, Ashish Kumar; Saud, Santosh (The Lumbini Journal of Business and Economics, 2022)
The study examines the impact of financial ratios, operational efficiency, and non-performing loan on the profitability of Nepalese commercial banks. Return on assets and Return on equity is selected as the dependent variables. The selected independent variables are leverage, liquidity ratio, net interest margin, capital adequacy ratio, non-performing loan, and operating efficiency. The study is based on secondary data of 20 commercial banks with 120 observations from 2015/16 to 2020/21. The data were collected from bank supervision reports published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks.. The correlation coefficients and regression models are estimated to test the significance and importance of financial ratios, operational efficiency, and non-performing loan on the profitability of Nepalese commercial banks. The study showed that leverage and operating efficiency has a negative impact on return on assets. It indicates that increased leverage and operating efficiency leads to a decrease in return on assets. Similarly, liquidity ratio, net interest margin, capital adequacy ratio and the non-performing loan has a positive impact on return on assets. It indicates that the higher the liquidity ratio, net interest margin, capital adequacy ratio and non-performing loan, the higher would be the return on assets. Likewise, leverage, liquidity ratio and net interest margin has a positive impact on return on equity. It indicates that an increase in leverage, liquidity ratio, and net interest margin leads to an increase in return on equity. Furthermore, capital adequacy ratio, non-performing loan, and operating efficiency has a negative impact on return on equity. It indicates that an increase in capital adequacy ratio, non-performing loan and operating efficiency leads to decreasing in return on equity.